2016
DOI: 10.3762/bjoc.12.225
|View full text |Cite
|
Sign up to set email alerts
|

A detailed view on 1,8-cineol biosynthesis by Streptomyces clavuligerus

Abstract: The stereochemical course of the cyclisation reaction catalysed by the bacterial 1,8-cineol synthase from Streptomyces clavuligerus was investigated using stereospecifically deuterated substrates. In contrast to the well investigated plant enzyme from Salvia officinalis, the reaction proceeds via (S)-linalyl diphosphate and the (S)-terpinyl cation, while the final cyclisation reaction is in both cases a syn addition, as could be shown by incubation of (2-13C)geranyl diphosphate in deuterium oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 41 publications
0
39
0
7
Order By: Relevance
“…Notably, the two different mechanisms can be distinguished using enantioselectively deuterated GPP, with either the 1‐ pro ‐ S hydrogen atom (red) or the 1‐ pro ‐ R hydrogen atom (blue) being substituted by a deuterium atom, because these deuterium labels end up in diastereotopic positions in 15 ( exo or endo , respectively). Incubation of ( R )‐ and ( S )‐(1‐ 2 H)GPP with the 1,8‐cineol synthase from S. clavuligerus revealed a cyclisation mechanism via the intermediates of Scheme A . Further experiments with (2‐ 13 C)GPP in deuterium oxide revealed that the conversion from 13 to 14 may indeed proceed by intramolecular proton transfer, because the introduced deuterium labelling in 15 (green hydrogen atom) specifically ended up in the exo position, as was determined by HSQC spectroscopy (in this experiment the 13 C label was introduced for a highly sensitive signal detection).…”
Section: Monoterpene Cyclasesmentioning
confidence: 53%
See 3 more Smart Citations
“…Notably, the two different mechanisms can be distinguished using enantioselectively deuterated GPP, with either the 1‐ pro ‐ S hydrogen atom (red) or the 1‐ pro ‐ R hydrogen atom (blue) being substituted by a deuterium atom, because these deuterium labels end up in diastereotopic positions in 15 ( exo or endo , respectively). Incubation of ( R )‐ and ( S )‐(1‐ 2 H)GPP with the 1,8‐cineol synthase from S. clavuligerus revealed a cyclisation mechanism via the intermediates of Scheme A . Further experiments with (2‐ 13 C)GPP in deuterium oxide revealed that the conversion from 13 to 14 may indeed proceed by intramolecular proton transfer, because the introduced deuterium labelling in 15 (green hydrogen atom) specifically ended up in the exo position, as was determined by HSQC spectroscopy (in this experiment the 13 C label was introduced for a highly sensitive signal detection).…”
Section: Monoterpene Cyclasesmentioning
confidence: 53%
“…Incubation of (R)-and (S)-(1-2 H)GPP with the 1,8-cineol synthase from S. clavuligerus revealed a cyclisation mechanism via the intermediates of Scheme 4A. [30] Further experiments with (2-13 C)GPP in deuterium oxide revealed that the conversion from 13 to 14 may indeed proceed by intramolecular proton transfer, because the introduced deuterium labelling in 15 (green hydrogen atom) specifically ended up in the exo position, as was determined by HSQC spectroscopy (in this experiment the 13 C label was introduced for a highly sensitive signal detection). Notably, the 1,8-cineol synthase from S. officinalis was shown by similar labelling experiments to catalyse a cyclisation cascade via (R)-11 and (R)-12, also possibly with intramolecular proton transfer from 13 to 14, [31] which reflects the observation that terpenes from plants frequently resemble the optical antipodes of bacterial terpenes.…”
Section: Biosynthesis Of 18-cineolmentioning
confidence: 94%
See 2 more Smart Citations
“…This is in agreement with the predicted formation of the (S)-(À)-a-terpineol intermediate in simulations involving bCinS (See Experimental Section and Figure S6) and a previous isotope labelling study confirming (S)-a-terpinyl as intermediate. [18] So not only is bCinS able to tightly control the Asn305 assisted water attack of the a-terpinyl cation, it is also able to control the formation and stabilisation of a single linalyl diphosphate isomer intermediate in the early stages of the cyclisation cascade, ultimately leading to almost pure cineole formation.…”
Section: Resultsmentioning
confidence: 99%